A new species of Hygrocybe (Hygrophoraceae, Agaricales) from Kerala State, India - Latha, K. P. Deepna; Haridev, P.; Raj, K. N. Anil; Manimohan, Patinjareveettil (Phytotaxa, 2023)
Hygrocybe snigdha sp. nov. is described from Kerala State, India, based on both morphology and molecular phylogeny. This species is characterized by small basidiocarps with a deep red, strongly viscid pileus with an orange-white margin, dimorphic basidiospores and basidia, lamella-edges with abundant pseudocystidia, and an ixocutis-type pileipellis and stipitipellis. The phylogenetic analyses based on independent data matrices of the internal transcribed spacer (nrITS) and nuclear large subunit (nrLSU) of the ribosomal gene confirmed the novelty and the taxonomic position of H. snigdha within the section Velosae of the subgenus Hygrocybe. A comprehensive description of this new species is provided, along with comparisons with phenetically and phylogenetically related species, photographs of the basidiocarps, line drawings of the microscopic structures, and phylograms showing the infrageneric placement of the new species.